Respuesta :
Answer:
[tex]f^{-1}=+-\sqrt{x+1}[/tex]
Step-by-step explanation:
f(x) = x^2 -1
We need to find f^-1(x)
WE find inverse of f(x)
Replace f(x) with y
[tex]y= x^2 -1[/tex]
Replace x with y and y with x
[tex]x= y^2 -1[/tex]
Solve for y
add 1 on both sides , [tex]x+1= y^2[/tex]
To remove square , take square root on both sides
[tex]\sqrt{x+1} =\sqrt{y^2}[/tex]
[tex]\sqrt{x+1} =y[/tex]
[tex]y=+-\sqrt{x+1}[/tex]
Replace y with f^-1
[tex]f^{-1}=+-\sqrt{x+1}[/tex]
Answer:
Inverse function is
[tex]f^{-1}(x)=\pm \sqrt{x+1}[/tex]
Step-by-step explanation:
Given that [tex]f(x)=x^2-1[/tex]
Now using that equation of f(x), we need to find equation of the inverse function
[tex]f(x)=x^2-1[/tex]
[tex]f^{-1}(x)[/tex]
Step 1: Replace [tex]f^{-1}(x)[/tex] with y
[tex]y=x^2-1[/tex]
Step 2: Switchx and y
[tex]x=y^2-1[/tex]
Step 3: Solve for y
[tex]x=y^2-1[/tex]
[tex]x+1=y^2-1+1[/tex]
[tex]x+1=y^2[/tex]
[tex]y^2=x+1[/tex]
take square root of both sides
[tex]y=\pm \sqrt{x+1}[/tex]
Hence inverse function is
[tex]f^{-1}(x)=\pm \sqrt{x+1}[/tex]